Fibroblast Growth Factor Receptor 1-4 Genetic Aberrations as Clinically Relevant Biomarkers in Squamous Cell Lung Cancer - Moes-Sosnowska, Joanna; Chorostowska-Wynimko, Joanna (Frontiers in Oncology, 2022)
Fibroblast growth factor receptor (FGFR) inhibitors (FGFRis) are a potential therapeutic option for squamous non-small cell lung cancer (Sq-NSCLC). Because appropriate patient selection is needed for targeted therapy, molecular profiling is key to discovering candidate biomarker(s). Multiple FGFR aberrations are present in Sq-NSCLC tumors—alterations (mutations and fusions), amplification and mRNA/protein overexpression—but their predictive potential is unclear. Although FGFR1 amplification reliability was unsatisfactory, FGFR mRNA overexpression, mutations, and fusions are promising. However, currently their discriminatory power is insufficient, and the available clinical data are from small groups of Sq-NSCLC patients. Here, we focus on FGFR aberrations as predictive biomarkers for FGFR-targeting agents in Sq-NSCLC. Known and suggested molecular determinants of FGFRi resistance are also discussed.